WAYLA: novel gaming experience through unique gaze interaction - Chang, Wein (2019)
An eye tracker is a device that tracks a user's eye gaze when interacting with external world. It has mostly been used as a tool for psychology or market research to provide insights of users’ viewing behaviors. Few attempts have been made to integrate eye trackers into video games. However, eye trackers were simply treated as alternative input devices to a mouse or a joystick. Eye gaze based interaction for gaming has the potential to offer experiences which are not available through other interaction mechanisms. WAYLA is an original game designed to achieve this purpose.